Physical and chemical properties of wami tilapia skin gelatin - Alexandre Da Trindade Alfaro (Food Science and Technology, 2013)
Gelatin was extracted from the skin of tilapia (Oreochromis urolepis hornorum) and characterized according to its physical and chemical properties. It had pH 4.66, which is slightly higher than the values reported for gelatins processed by acid solubilization. In general, the ionic content was low, and the average yield of the process was 5.10 g/100 g. The proximal composition of the gelatin was similar to that of the commercial gelatins, with slightly higher moisture content. The tilapia skin gelatin had whitish-yellow color and average turbidity of 67 NTU.